2023
DOI: 10.1101/2023.09.01.555924
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Localization of four class I glutaredoxins in the cytosol and the secretory pathway and characterization of their biochemical diversification

Michelle Schlößer,
Anna Moseler,
Yana Bodnar
et al.

Abstract: Class I glutaredoxins (GRXs) are catalytically active oxidoreductases and considered key proteins mediating reversible glutathionylation and deglutathionylation of protein thiols during development and stress responses. To narrow in on putative target proteins, it is mandatory to know the subcellular localization of the respective GRXs and to understand their catalytic activities and putative redundancy between isoforms in the same compartment. We show that GRXC1 and GRXC2 are cytosolic proteins with GRXC1 bei… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…roGFP2 can be used as a topology sensor due to the strong glutathione redox difference between the cytosol (Fig. 9e) and endomembrane lumen (Brach et al, 2009;Schl€ oßer et al, 2024) (Fig. 9f).…”
Section: Resultsmentioning
confidence: 99%
“…roGFP2 can be used as a topology sensor due to the strong glutathione redox difference between the cytosol (Fig. 9e) and endomembrane lumen (Brach et al, 2009;Schl€ oßer et al, 2024) (Fig. 9f).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we found a trend for increased total GSH content, which would according to the Nernst equation suggest more negative E GSH , although HPLC measurements do not allow for subcellular resolution. A shift of roGFP2 thiol/disulfide redox state to more oxidized values usually reveals an oxidative shift in E GSH , as roGFP2 specificity for the glutathione/GRX system was tested in vitro and in vivo [ 29 , 41 , 65 , 75 ]. Particularly, inefficient reduction of GSSG caused by absence of GR leads to an increase of OxD roGFP2 in the same subcellular compartment [ 39 , 40 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found a trend for increased total GSH content, which would according to the Nernst equation suggest more negative E GSH , although HPLC measurements do not allow for subcellular resolution. A shift of roGFP2 thiol/disulfide redox state to more oxidized values usually reveals an oxidative shift in E GSH , as roGFP2 specificity for the glutathione/GRX system was tested in vitro and in vivo (Meyer et al, 2007; Begas et al, 2017; Trnka et al, 2020; Schlößer et al, 2023). Thus, inefficient reduction of GSSG caused by absence of glutathione reductase (GR) leads to an increase of OxD roGFP2 in the same subcellular compartment (Marty et al, 2009; Marty et al, 2019; Müller-Schüssele et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Partial redundancy between the GSH/GRX and TRX redox systems was also demonstrated in plants, regarding the cytosol and mitochondrial matrix (Marty et al, 2009), but not for the plastid stroma (Marty et al, 2019). Regarding mutants lacking all class I GRX of one compartment, double null mutants of A. thaliana lacking cytosolic GRXC1 and GRXC2 were originally described to be lethal (Riondet et al, 2012) but have recently been reported to be viable and with a WT-like phenotype (Schlößer et al, 2023). In the secretory pathway, which lacks a GR and thus possesses a less reducing E GSH , double mutants of GRXC3/GRXC4 grow normally (Schlößer et al, 2023) but showed decreased hypocotyl length compared to WT when grown in elevated temperature (Dard et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation